Analisa Hukum Terhadap Perjanjian Kerjasama Pengelolaan Pas Masuk Terminal Penumpang Dalam Negeri di Pelabuhan Sri Bintan Pura Tanjung Pinang - Suryadi Suryadi (Jurnal Selat, 2014)
The purpose of granting regional autonomy is to empower the region in the form of improving care, protection, welfare, initiative, creativity, and community participation in development, foster democracy, equity and justice, and unity, unity, and national harmony in the remembrance of the origin of an area, diversity and characteristics, as well as potential areas that lead to the improvement of the welfare of the people in the system of the Republic of Indonesia. In that regard, it has been made Cooperation Agreement between PT. (Persero) IPC I Branch Tanjung Pinang Tanjung Pinang with the City Government B.XIV-1/TPI-US.15 Numbers and Number 552.3/091.A/HUBLA signed on March 15, 2011 on the Management of Pas Log of Domestic Passenger Terminal in port of Sri Bintan Pura Tanjung Pinang. Examined in this study are some of the regulations that form the basis of law in the cooperation agreement which according to the author it is important to study whether the regulation is used as a legal basis in the agreement is appropriate or not. Also on the principles and factors that must be considered in the drafting of the contract. Methods The approach used in this study is normative methods. From these results it can be concluded that in principle any drafting the contract is to be an agreement of the parties ranging from the use of the term contract until the dispute settlement while referring to the legislation in force, is not contrary to public order and decency. Factors that must be considered by the parties and will hold the legal authority to make the contract are the parties, taxation, over a legal right, the problem keagrarian, choice of law, dispute resolution, termination of contract, and the agreed standard form of agreement. That the legal basis used by PT. IPC I (Persero) Branch Tanjung Pinang in the partnership agreement is in conformity with the applicable regulations. That the legal basis used by the Local Government Tanjungpinang in the partnership agreement does not conform and contrary to regulations. Keywords: Regional Autonomy, Ports and Cooperation Agreement.